2018
DOI: 10.3747/co.25.4083
|View full text |Cite
|
Sign up to set email alerts
|

Eastern Canadian Colorectal Cancer Consensus Conference 2017

Abstract: The annual Eastern Canadian Gastrointestinal Cancer Consensus Conference 2017 was held in St. John's, Newfoundland and Labrador, 28-30 September. Experts in radiation oncology, medical oncology, surgical oncology, and cancer genetics who are involved in the management of patients with gastrointestinal malignancies participated in presentations and discussion sessions for the purpose of developing the recommendations presented here. This consensus statement addresses multiple topics in the management of gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 108 publications
1
0
0
Order By: Relevance
“…Extended RAS mutation status was captured for 98.6% of the patients, with 60.0% of the patients overall (n = 430) being classified as RAS mutant; 38.6% (n = 277), as RAS wild-type; and 1.4% (n = 10), as RAS status unknown. The high rate of RAS mutation testing is clinically meaningful and conforms to the recommendations published by expert Canadian groups [29][30][31] .…”
Section: Patient and Disease Characteristicssupporting
confidence: 68%
“…Extended RAS mutation status was captured for 98.6% of the patients, with 60.0% of the patients overall (n = 430) being classified as RAS mutant; 38.6% (n = 277), as RAS wild-type; and 1.4% (n = 10), as RAS status unknown. The high rate of RAS mutation testing is clinically meaningful and conforms to the recommendations published by expert Canadian groups [29][30][31] .…”
Section: Patient and Disease Characteristicssupporting
confidence: 68%
“…Post hoc retrospective analysis of pivotal trials and several meta-analyses have demonstrated overall survival (OS) improvements with the addition of EGFR inhibitors to chemotherapy versus chemotherapy +/− bevacizumab in patients with 1L RAS wild-type (WT) left-sided mCRC [ 12 , 13 , 14 , 15 , 16 ]. As such, clinical and molecular markers including PTL should be taken into consideration to guide treatment decisions related to 1L mCRC, as recommended by clinical practice guidelines [ 17 , 18 ] and several Canadian consensus papers [ 19 , 20 , 21 , 22 , 23 ]. The randomized controlled phase 3 PARADIGM study prospectively demonstrated that panitumumab added to mFOLFOX6 led to a median OS benefit of 3.6 months in the left-sided population over bevacizumab plus mFOLFOX6 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%